Thinking Mathematically (6th Edition)

Published by Pearson
ISBN 10: 0321867327
ISBN 13: 978-0-32186-732-2

Chapter 6 - Algebra: Equations and Inequalities - 6.1 Algebraic Expressions and Formulas - Exercise Set 6.1: 25

Answer

27

Work Step by Step

Given 2$x^{2}$ - 5x -6, x=-3 Step 1: Put the value of x=-3 for each x in the expression =2$(-3)^{2}$ - 5(-3) -6 Step 2: Evaluate the exponential expression$(-3)^{2}$ = (-3)(-3) = 9 =2( 9)-5(-3)-6 Step 3: Multiply 2(9) = 18 and 5(-3)= -15 =18 +15-6 Step 4: Add and Subtract from left to right first add 18+15 = 33 33-6 subtract 27
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.